The practice of child adoption without court determination - Ridwan, Mahlil (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
The problem analyzed is the implementation of child adoption without a court order. Child adoption is usually carried out by people whose marriage does not produce offspring. The process of child adoption in Indonesia has been regulated in Government Regulation No. 54/2007 on the Implementation of Child Adoption and Minister of Social Affairs Regulation No. 110/HUK/2009 on Requirements for Child Adoption. However, in practice there are still implementations of child adoption that are not in accordance with the regulations. This research aims to explain how the practice of child adoption is carried out by the people of Tadu Raya Subdistrict and how the Indonesian legal system reviews the implementation of child adoption. This research uses juridical-empirical method. The results of this study show that the implementation of child adoption in Tadu Raya Subdistrict is only through an oral agreement process between the adoptive parents and the child's biological parents with the factor of not having children in the family, as well as the economic factors of the biological family causing compassion to adopt the child, the adopted child is also positioned as a biological child even though the relationship with his biological parents is not disconnected. In the Indonesian legal system, the practice of child adoption is not in accordance with positive law and Islamic law. The conclusion of this research is that the practice of child adoption in Tadu Raya Sub-district is not in accordance with the court decision process.